Software Engineering, Business Continuity, and Education International Conferences, ASEA, DRBC and EL 2011, Held as Part of the Future Generation Information Technology Conference, FGIT 2011, in Conjunction with GDC 2011, Jeju Island, Korea, December 8-10, 2011. Proceedings - Kim, Tai-hoon; Adeli, Hojjat; Kim, Haeng-Kon; Kang, Heau-jo; Kim, Kyung Jung; Kiumi, Akingbehin; Kang, Byeong-Ho (Communications in Computer and Information Science,, 2011)
This book comprises selected papers of the International Conferences, ASEA, DRBC and EL 2011, held as Part of the Future Generation Information Technology Conference, FGIT 2011, in Conjunction with GDC 2011, Jeju Island, Korea, in December 2011. The papers presented were carefully reviewed and selected from numerous submissions and focuse on the various aspects of advances in software engineering and its Application, disaster recovery and business continuity, education and learning.